The use of letter card game media to develop the ability to recognize letters in children aged 4-5 years at Darul Falah Kindergarten 10 Samarinda - Ardiana, Reni; Aslindah, Andi; Agustina, Rinawati (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Learning media is one of the learning tools used and the importance of its presence in the classroom. Moreover, in early childhood education institutions, where children need media that can help children understand the material provided by the teacher. One of the media that can be used to help children recognize letters is the letter card game. Learning letters is an essential component of literacy development. The formulation of the problem in this research is how to use letter card game media to develop the ability to recognize letters in children aged 4-5 years? This research aims to provide an overview of the use of letter card media for children's letter recognition abilities in kindergarten. This research uses a qualitative approach, namely describing and explaining the use of letter card game media in developing the ability to recognize letters in AUD. The subjects in this research were the children of Darul Falah 10 Samarinda Kindergarten. It is hoped that the results of this research can develop children's ability to recognize letters. The benefit of this writing is to increase reade